Relação(ões) entre a análise do comportamento e as ciências biológicas e o papel das variáveis orgânicas na constituição do comportamento e no atendimento dos objetivos da análise do comportamento - Prado, Rita de Cássia Ponte (2012)
The present work aims to answer two questions: 1- What is (are) the relation (s) between behavior analysis and biological sciences? And 2- The organical variables have an important role in the: constitution and/or comprehension and/or description and/or explanation and/or prediction and behaviour control by behaviour analysis? For this purpose, a sample of a literature was created to meet the search criteria and selection of references. Both of the texts comprising this sample were analized in order to identify passages related to the question 1 as well as those related to the question 2. The passages related to the question 1 were categorized in accordance with the independence relationships, complementarity and integration. Following this discussion, these same passages were categorized through notes which included either the relation considered by the categorization and also the arguments comprised by the passages in order to defend the relationship addressed. The passages referring to question 2 were categorized through 6 notes, which were constituted by sentences addressed to the participation (or not) of organical variables in the constitution of behaviour and meeting the goals of behaviour analysis. From such procedure, and based in the different results obtained, was possible to identify that the behaviour analysis and the biological sciences are both independent and complementary, and can integrate each other. With regards to the role/function delegated to de organical variables by behavioural analysis, it is possible to infer that these variables are adressed as constitutives in the behavioural process and in respect of their roles to meet the goals of behavioral analysis, was identified the existence of divergent opinions among the analized authors some conceive that such variables have a relevant role in order to meet these goals while others rather think the opposite. Although there are divergences, it was found that a major number of authors defended the use of these variables to meet the goals of behaviour analysis